Selection of Intermittent Irrigation to Increase Growth and Yield of Some Local Rice Varieties (Oryza sativa L.) in the Rainy Season - Isnawan, Bambang; Hariyono, Hariyono; Gumilar, Aldi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
This study aims to examine the influence of various varieties and methods of irrigation on the response to rice growth and yield. The research was conducted in the Experimental Land of the Faculty of Agriculture, University of Muhammadiyah Yogyakarta, in January 2020. The study was conducted in the area using a factorial strip plot design in a Randomized Completely Block Design with three replications. Thirty-six experimental units were obtained. This research consists of two factors. Factor I consists of 4 methods of irrigation, namely continuous flooding, ten days flooding, six dry days, eight days flooding, eight dry days, and six days flooding, ten dry days. Factor II consists of 3 varieties: Ciherang, Cempo Hitam, and Mentik Susu. The observed parameters are the height of plants, number of tillers, leaves area, length of roots, fresh weight of plants, dry weight of plants, harvest index, panicle number, and weight of grain/ hectare. This study showed that Cempo Hitam and Mentik Susu varietas rice plants were higher, and the leaves were more expansive than the Ciherang variety. Irrigation does not affect plant height, number of tillers, leaf area, root length, or rice panicles. There is a mutual influence between variety with irrigation on the fresh and dry weight of rice plants, panicle length, harvest index, and yield per hectare of rice. A variety of Mentik Susu with conventional irrigation, ten days flooded, six days dry, six days flooded, and ten days dry, showed higher yields per hectare compared to the combination of other varieties and irrigations.